Ionic liquid impregnated porous organic silicon ice-resistant coating as well as preparation method and application thereof

By introducing monovinyl monohydrogen-terminated polydimethylsiloxane and sodium chloride salt particles into the polydimethylsiloxane coating, combined with salt template method and ionic liquid infiltration technology, a porous structure coating was prepared, which solved the problem of high ice adhesion strength of traditional coatings in low temperature environments, and achieved significant improvement in ice resistance.

CN119592221APending Publication Date: 2025-03-11NAT INNOVATION INST OF DEFENSE TECH PLA ACAD OF MILITARY SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411901400.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Traditional polydimethylsiloxane coatings have high ice adhesion strength in low temperature environments, which limits its application in the field of anti-icing.

Method used

Porous structures were prepared by introducing monovinyl monohydrogen-terminated polydimethylsiloxane and sodium chloride salt particles, combined with salt template method, and infiltrated using ionic liquids to adjust the cross-linking density and porous structure of the coating to reduce ice adhesion strength.

Benefits of technology

In an environment of -20°C, the freezing time of water droplets is extended by 6.4 times, the ice adhesion strength is reduced, and the ice resistance of the coating is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592221A_ABST
    Figure CN119592221A_ABST
Patent Text Reader

Abstract

The invention discloses an ionic liquid impregnated porous organic silicon ice-resistant coating as well as a preparation method and application thereof. The coating is a polymer prepared from polydimethylsiloxane, monovinyl monohydrogen terminated polydimethylsiloxane, a cross-linking agent, salt particles and ionic liquid. Wherein the polydimethylsiloxane, vinyl on the monovinyl monohydrogen-terminated polydimethylsiloxane and silicon-hydrogen bonds on the cross-linking agent are subjected to a condensation polymerization reaction to form a polymer. The resulting polymer has high compressibility, imbibition, hydrophobicity and ice resistance, in particular in terms of ice resistance. The porous coating can prolong the freezing time of water drops by 6.4 times in a low-temperature environment at-20 DEG C, large-scale ionic liquid imbibition can also be carried out, and after the ionic liquid is imbibed, the ice adhesion strength is reduced to 8.5 kPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer coatings and preparation thereof, in particular to an ionic liquid impregnated porous organosilicon anti-icing coating and a preparation method and application thereof. Background Art

[0002] Ice formation and accumulation on solid surfaces exposed to low temperatures can have an adverse impact on a series of production activities and cause significant economic losses, including aviation, shipping, transportation and power systems. Although traditional active de-icing technology has a certain effect in de-icing, it has the disadvantages of high energy consumption or pollution. Therefore, the demand for passive anti-icing technology has increased dramatically. In the face of this problem, polydimethylsiloxane (PDMS) coating is a solution with great anti-icing potential. It can reduce the bonding strength between ice and the surface through component optimization and structural design.

[0003] Polydimethylsiloxane (PDMS) is known for its excellent optical transparency, chemical stability and low surface energy, which can ensure long-term stability. However, the large ice adhesion of traditional polydimethylsiloxane coatings severely limits its application. The ice adhesion strength of the coating can be reduced by introducing monovinyl monohydrogen-terminated polydimethylsiloxane (vt-PDMS) into the PDMS network and adjusting its cross-linking degree. At the same time, a porous structure is designed for it, and a porous polydimethylsiloxane coating (PV-PDMS) is prepared using a salt template method. At the same time, ionic liquid (IL) infiltration is carried out to obtain a liquid-infiltrated porous polydimethylsiloxane coating (PV-PDMS / IL), which is expected to further reduce the ice adhesion strength. Summary of the invention

[0004] In view of the problems existing in the prior art, in order to reduce the ice adhesion strength of the polymer coating and achieve long-term anti-icing, the present invention proposes a method for preparing a polymer porous coating using polydimethylsiloxane (PDMS) and monovinyl monohydrogen-terminated polydimethylsiloxane (vt-PDMS), a crosslinking agent, sodium chloride salt particles (NaCl) and ionic liquid (IL) as raw materials. The polymer coating is an anti-icing porous polymer composite material with multiple properties, including high compressibility, swellability, and anti-icing. In an environment of -20°C, the surface ice adhesion strength can be reduced by infiltration with ionic liquid (IL).

[0005] To achieve the above-mentioned purpose, in a first aspect, the present invention provides a porous organosilicon anti-icing coating impregnated with an ionic liquid, wherein the coating is a polymer prepared by using polydimethylsiloxane and monovinyl monohydrogen-terminated polydimethylsiloxane, a crosslinking agent, sodium chloride salt particles and an ionic liquid; wherein the vinyl groups on the polydimethylsiloxane and the monovinyl monohydrogen-terminated polydimethylsiloxane and the silicon-hydrogen bonds on the crosslinking agent undergo a condensation reaction to form a polymer.

[0006] Furthermore, the salt particles are sodium chloride salt particles; the ionic liquid is 1-octyl-3-methylimidazolium tetrafluoroborate; and the polymer is a porous polydimethylsiloxane composite polymer with controlled crosslinking density prepared by using polydimethylsiloxane and monovinyl monohydrogen-terminated polydimethylsiloxane, a crosslinking agent, sodium chloride salt particles and ionic liquid.

[0007] Furthermore, the polydimethylsiloxane is a chain polymer, namely Sylgard 184; the monovinyl monohydrogen terminated polydimethylsiloxane is a chain polymer, and its average viscosity is 40-60 cSt.

[0008] In an alternative scheme, the present invention provides an ionic liquid-impregnated organic silicon anti-ice porous coating, wherein the coating is a polymer prepared using polydimethylsiloxane and monovinyl monohydrogen-terminated polydimethylsiloxane, a crosslinker, salt particles and an ionic liquid; wherein the vinyl groups on the polydimethylsiloxane and the monovinyl monohydrogen-terminated polydimethylsiloxane and the silicon-hydrogen bonds on the crosslinker undergo a condensation reaction to form a polymer.

[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned porous organosilicon anti-icing coating impregnated with ionic liquid, the preparation method comprising the following steps:

[0010] S1. The polydimethylsiloxane, the monovinyl monohydrogen-terminated polydimethylsiloxane and the crosslinking agent are completely mixed under magnetic stirring conditions to obtain a mixed solution;

[0011] S2. adding sodium chloride salt particles to the mixed solution, and obtaining a uniform PV-PDMS prepolymer solution after magnetic stirring;

[0012] S3. The PV-PDMS prepolymer solution is heated to obtain a PV-PDMS salt-containing coating;

[0013] S4. removing salt particles from the PV-PDMS salt-containing coating in a water bath at a predetermined temperature;

[0014] S5. Drying the PV-PDMS coating after removing the salt particles in an oven;

[0015] S6. Completely immerse the dried PV-PDMS coating in the ionic liquid solution, and obtain the PV-PDMS / IL coating after complete swelling.

[0016] Furthermore, in step S1, the ratio of polydimethylsiloxane, monovinyl monohydrogen terminated polydimethylsiloxane and crosslinking agent is (10-a):a:1, wherein a is the ratio of monovinyl monohydrogen terminated polydimethylsiloxane added, and a=2-8.

[0017] Furthermore, the polydimethylsiloxane is a chain polymer, namely Sylgard 184; the monovinyl monohydrogen terminated polydimethylsiloxane is a chain polymer, and its average viscosity is 40-60 cSt.

[0018] Further, in step S2, the mass ratio of sodium chloride salt particles to the mixed solution is 4:1

[0019] Furthermore, the stirring parameters in steps S1 and S2 are as follows: the PV-PDMS prepolymer solution is subjected to magnetic stirring for 5 minutes, and the magnetic stirring parameter is set to 800-1000 rpm to obtain a uniform PV-PDMS prepolymer solution.

[0020] Furthermore, the heating parameters in step S3 are as follows: the heating temperature is set to 60-80° C., the duration is 4 hours, and the PV-PDMS salt-containing coating is obtained.

[0021] Furthermore, the predetermined temperature water bath parameters in step S4 are as follows: the PV-PDMS salt-containing coating is treated in a water bath at 60-80° C. for 3 days, wherein the water used in the water bath is replaced every 8 hours.

[0022] Further, in step S5, drying is performed in a blast drying oven at a temperature of 60-80 degrees Celsius for 4 hours.

[0023] Furthermore, the ionic liquid infiltration conditions in step S6 are as follows: infiltration in the ionic liquid for 4-8 hours.

[0024] In a third aspect, the present invention provides an application of an ionic liquid-impregnated porous organosilicon anti-icing coating, wherein the ionic liquid-impregnated porous organosilicon anti-icing coating can be applied to electronic components and / or structural parts that need to work in a cold environment below 0°C in the aviation field, marine engineering, power industry and / or aerospace field.

[0025] Furthermore, the coating is applied to electronic components and / or structural parts of aircraft, wind turbines, power transmission lines or outdoor electronic products used in cold regions, sailing ships, and offshore platforms. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The synthetic process flow chart of the ionic liquid impregnated porous organosilicon anti-icing coating of the present invention;

[0027] Figure 2 This is a microscopic image display of the porous organosilicon anti-icing coating in Example 1;

[0028] Figure 3 This is a diagram showing the anti-icing results of the porous organosilicon anti-icing coating in Example 1;

[0029] Figure 4 This is a diagram showing the deicing results of the porous organosilicon anti-icing coating in Example 1. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0032] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0033] The following combination Figure 1-Figure 4 The specific embodiments of the present invention are described in detail. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0034] In order to solve the problem of high ice adhesion strength when polymer coatings are used in the field of anti-icing, the present invention proposes a porous organosilicon anti-icing coating impregnated with ionic liquid, wherein the coating is a polymer coating prepared using polydimethylsiloxane (PDMS) and monovinyl monohydrogen-terminated polydimethylsiloxane (vt-PDMS), a crosslinker, salt particles and ionic liquid (IL) as raw materials. The polymer coating is a porous ionic liquid-impregnated polymer composite material, which has multiple properties, including high compressibility, swellability and ice resistance. In an environment of -20°C, the surface ice adhesion strength can be reduced by infiltration with ionic liquid (IL). The polydimethylsiloxane undergoes a condensation reaction with the vinyl group on the monovinyl monohydrogen-terminated polydimethylsiloxane and the silicon-hydrogen bond on the crosslinker to form a polymer. Specifically, the salt particles are sodium chloride tetraoxide salt particles; and the ionic liquid is 1-octyl-3-methylimidazole tetrafluoroborate. The polymer is a porous polydimethylsiloxane composite multifunctional polymer with controlled cross-linking density prepared by using polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane, a cross-linking agent, sodium chloride salt particles and an ionic liquid.

[0035] The porous organosilicon anti-icing coating impregnated with ionic liquid provided by the present invention has chemical components of polydimethylsiloxane and monovinyl monohydrogen-terminated polydimethylsiloxane, a crosslinker and an ionic liquid. The vinyl groups on polydimethylsiloxane and monovinyl monohydrogen-terminated polydimethylsiloxane and the silicon-hydrogen bonds on the crosslinker undergo polycondensation reactions to form polymers. Compared with traditional polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane lacks a segment of vinyl groups, so the introduction of monovinyl monohydrogen-terminated polydimethylsiloxane can reduce the crosslinking degree of the original polydimethylsiloxane polymer, thereby improving its anti-icing performance. The porous structure prepared by using sodium chloride salt particles and the salt template method can greatly reduce the thermal conductivity of the material, thereby reducing the freezing time of water droplets on its surface, thereby obtaining anti-icing ability. At the same time, the porous structure can further reduce the contact area between the surface and the ice and reduce the adhesion strength of the ice, thereby obtaining deicing ability. The sponge-like porous coating has great potential to absorb ionic liquid (IL), and by swelling the IL, the porous coating can further obtain better anti-icing effect. Ultimately, the freezing time can be extended by 6.4 times at -20℃, and the ice adhesion strength can be reduced to 8.5kPa.

[0036] The mass ratio of polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane and crosslinker is (10-a): a: 1, where a is the ratio of monovinyl monohydrogen-terminated polydimethylsiloxane added, and a=2-8. The crosslinking density and anti-icing performance of the coating are controlled by controlling the mass ratio of polydimethylsiloxane and monovinyl monohydrogen-terminated polydimethylsiloxane in the polymer. Before preparing the porous organosilicon anti-icing coating impregnated with ionic liquid, the component with the lowest ice adhesion strength is first explored in the mass ratio of polydimethylsiloxane and monovinyl monohydrogen-terminated polydimethylsiloxane, and then the porous anti-icing coating is prepared by using salt particles and salt template method with a prepolymer solution of PV-PDMS in the preferred ratio. For the field of anti-icing, the preferred mass ratio of polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane and crosslinker is 5:5:1. Among them, under the mass ratio of 5:5:1, increasing or decreasing the proportion of monovinyl monohydrogen terminated polydimethylsiloxane will increase the adhesion strength of ice.

[0037] The present invention also provides a method for preparing the anti-icing porous coating, such as Figure 1 As shown, the preparation method comprises the following steps:

[0038] S1. The polydimethylsiloxane, the monovinyl monohydrogen-terminated polydimethylsiloxane and the crosslinking agent are completely mixed under magnetic stirring conditions to obtain a mixed solution;

[0039] S2. adding sodium chloride salt particles to the mixed solution, and obtaining a uniform porous polydimethylsiloxane coating (PV-PDMS) prepolymer solution after magnetic stirring;

[0040] S3. The PV-PDMS prepolymer solution is heated to obtain a PV-PDMS salt-containing coating;

[0041] S4. removing salt particles from the PV-PDMS salt-containing coating in a water bath at a predetermined temperature;

[0042] S5. Drying the PV-PDMS coating after removing the salt particles in an oven;

[0043] S6. The dried PV-PDMS coating is completely immersed in the ionic liquid solution, and after complete swelling, a porous polydimethylsiloxane coating impregnated with the ionic liquid (PV-PDMS / IL) is obtained.

[0044] Preferably, in step S1, the ratio of polydimethylsiloxane, monovinyl monohydrogen terminated polydimethylsiloxane and cross-linking agent is 5:5:1.

[0045] Specifically, the polydimethylsiloxane is a chain polymer, and its product model is Sylgard184, and both ends of it are terminated by vinyl groups; monovinyl monohydrogen terminated polydimethylsiloxane is also a chain polymer, but one side is terminated by vinyl groups and the other side is terminated by hydrogen groups, and its average viscosity is 40-60 cSt.

[0046] Preferably, in step S2, the mass ratio of sodium chloride salt particles to the mixed solution is 4:1.

[0047] Preferably, the stirring parameters in steps S1 and S2 are as follows: the PV-PDMS prepolymer solution is subjected to magnetic stirring for 5 minutes, and the magnetic stirring parameter is set to 800-1000 rpm to obtain a uniform PV-PDMS prepolymer solution. Among them, the magnetic stirring parameter is set to 800 rpm for the best.

[0048] Preferably, the heating parameters in step S3 are as follows: the heating temperature is set to 60-80°C, the duration is 4 hours, and the PV-PDMS salt-containing coating is obtained. Among them, the heating temperature is set to 80°C, which is the best.

[0049] Preferably, the predetermined temperature water bath parameters in step S4 are as follows: the PV-PDMS salt-containing coating is treated in a water bath at 60-80°C for 3 days, wherein the water used in the water bath is replaced every 8 hours, wherein 80°C is the best.

[0050] Preferably, in step S5, the drying is carried out in a forced air drying oven at a temperature of 60-80 degrees Celsius for 4 hours, wherein 80 degrees Celsius is optimal. Specifically, in step S6, the ionic liquid is 1-octyl-3-methylimidazolium tetrafluoroborate.

[0051] Preferably, in step S6, the infiltration conditions are as follows: infiltration in the ionic liquid for 4-8 hours, wherein infiltration for 6 hours is optimal.

[0052] Figure 2 The microscopic image of the porous organosilicon anti-icing coating impregnated with the ionic liquid is shown; Figure 2 As shown in the figure, the internal microstructure morphology of the porous PV-PDMS coating prepared by the salt template method was tested by SEM. Figure 2 (i) shows an optical photo of PV-PDMS, and (ii) and (iii) show SEM images of its cross section. The PV-PDMS coating becomes white and opaque due to the porous structure on the surface and inside. Figure 2In (ii) and (iii), the porous structure left after the salt particles dissolve can be clearly seen, and its overall size is 100-400μm cube. The large number of visible pore structures gives the PV-PDMS coating great compressibility and the ability to absorb liquid, which provides great support for its anti-icing application.

[0053] Figure 3 The figure is a display diagram of the anti-icing result of the porous organic silicon anti-icing coating; Figure 3 As shown, the coating's ability to delay freezing and ice release was measured at a temperature of -20°C. Water droplets on the surface of traditional polydimethylsiloxane achieved freezing in 172.8±13.7 seconds. In contrast, the anti-icing porous coating of the present invention takes 1100.1±84.7 seconds to completely freeze from room temperature, and the freezing time is extended by nearly 1000s, which is 6.4 times longer than that of traditional polydimethylsiloxane coatings, showing excellent anti-icing performance. This is due to the significantly reduced thermal conductivity of the porous structure of the anti-icing porous coating, and the reduced contact area for heat transfer between water droplets and the material.

[0054] Figure 4 The deicing results of the porous organosilicon anti-icing coating impregnated with the ionic liquid are shown in the figure. When the mass ratio of polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane and cross-linking agent is 5:5:1, the ice adhesion strength reaches the lowest value of all tested ratios, reaching 45.3±1.2kPa. Therefore, the anti-icing porous coating is prepared using the preferred mass ratio. In the ice adhesion strength test, the introduction of the porous microstructure further reduces the ice adhesion strength of the anti-icing porous coating to 19.6±4.6kPa. This result can be attributed to the reduced contact area between the ice and the coating surface due to the porous structure. During the freezing process, the surface with sealed pores can prevent frozen water from penetrating into the structure. Importantly, by further immersing the anti-icing porous coating in the ionic liquid, the ice adhesion strength of the obtained PV-PDMS / IL coating reaches 9.5±2.4kPa, showing excellent deicing performance.

[0055] In order to achieve a long-lasting anti-icing effect, monovinyl monohydrogen-terminated polydimethylsiloxane and porous structure were introduced into the traditional polydimethylsiloxane material system. Polymers were formed by condensation reaction between the vinyl groups on polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane and the silicon-hydrogen bonds on the crosslinker, while the crosslinking density of the traditional polydimethylsiloxane network was regulated. The introduction of sodium chloride salt particles and salt templates brought internal and surface structures to the coating, which gave the coating great compressibility, swellability and anti-icing properties. After absorbing ionic liquids, its anti-icing performance was greatly enhanced.

[0056] The ionic liquid impregnated porous organosilicon anti-icing coating is an anti-icing porous polymer coating prepared by using polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane, crosslinking agent, salt particles and ionic liquid. The polymer coating has high compressibility, swelling, hydrophobicity and ice resistance, especially in anti-icing. It can be used in the aviation field, marine engineering, power industry and aerospace field; especially suitable for electronic components and structural parts that need to work in cold environments, such as aircraft, wind turbines, transmission lines or outdoor electronic products used in cold areas, sailing ships, offshore work platforms, etc.

[0057] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the anti-icing performance of the anti-icing porous polymer coating is described. The technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0058] Example 1

[0059] 1.5g of polydimethylsiloxane, 1.5g of monovinyl monohydrogen-terminated polydimethylsiloxane, and 0.3g of a cross-linking agent were added to a beaker, and a mixed solution was prepared after magnetic stirring for 5 minutes. Then 13.2g of sodium chloride salt particles were added, and magnetic stirring was performed again for 5 minutes to obtain a uniform PV-PDMS prepolymer solution. The PV-PDMS prepolymer solution was evenly coated on the surface of the substrate and compacted, and cured at 80°C for 4 hours at normal pressure to obtain a porous coating containing salt particles. The porous coating containing salt particles was then placed in an 80°C water bath for 72 hours, wherein the water in the water bath needed to be replaced every 8 hours to completely remove the salt particles therein. Afterwards, it was dried in a blast drying oven at 80°C for 4 hours to obtain a porous coating. Finally, it was completely immersed in the ionic liquid for 6 hours to obtain the ionic liquid-impregnated porous silicone anti-icing coating.

[0060] The obtained prepolymer solution (5:5:1) is directly cured to obtain a cross-linked polydimethylsiloxane coating. At -20°C, the result of ice adhesion strength test of this example is 37.93±5.05 kPa.

[0061] Figure 3 , Figure 4 The test results of the anti-icing and anti-icing properties of the anti-icing porous coating described in Example 1 at -20°C are shown. Figure 3As shown, at -20°C, water droplets on the traditional polydimethylsiloxane surface require 172.8±13.7 seconds to freeze. In contrast, the anti-icing porous coating requires 1100.1±84.7 seconds to completely freeze from room temperature, and the freezing time is extended by nearly 1000s, which is 6.4 times longer than that of the traditional polydimethylsiloxane coating. Using glass as the test sample, the ice adhesion strength of the obtained PV-PDMS / IL coating reached 9.5±2.4kPa, showing excellent deicing performance.

[0062] Example 2

[0063] 2.4g of polydimethylsiloxane, 0.6g of monovinyl monohydrogen-terminated polydimethylsiloxane, and 0.3g of cross-linking agent were added to a beaker, and a mixed solution was prepared after magnetic stirring for 5 minutes. (If the mixed solution is directly cured at 80°C and normal pressure for 4 hours, a cross-linked polydimethylsiloxane coating obtained by direct curing of a prepolymer solution with a ratio of 8:2:1 can be obtained.) Then 13.2g of sodium chloride salt particles were added, and magnetic stirring was performed again for 5 minutes to obtain a uniform PV-PDMS prepolymer solution. The PV-PDMS prepolymer solution was uniformly coated on the surface of the substrate and compacted, and cured at 80°C and normal pressure for 4 hours to obtain a porous coating containing salt particles. The porous coating containing salt particles was then placed in an 80°C water bath for 72 hours, and the water in the water bath needed to be replaced every 8 hours to completely remove the salt particles. After that, it was dried in a blast drying oven at 80°C for 4 hours to obtain a porous coating. Finally, the ionic liquid was completely immersed in the ionic liquid for 6 hours to obtain the porous organosilicon anti-icing coating impregnated with the ionic liquid.

[0064] The obtained prepolymer solution (8:2:1) is directly cured to obtain a cross-linked polydimethylsiloxane coating. At -20°C, the result of ice adhesion strength test of this example is 71.25±2.05 kPa.

[0065] Example 3

[0066] 1.8g of polydimethylsiloxane, 1.2g of monovinyl monohydrogen-terminated polydimethylsiloxane, and 0.3g of cross-linking agent were added to a beaker, and a mixed solution was prepared after magnetic stirring for 5 minutes. (If the mixed solution is directly cured at 80°C and normal pressure for 4 hours, a cross-linked polydimethylsiloxane coating obtained by direct curing of a prepolymer solution with a ratio of 6:4:1 can be obtained.) Then 13.2g of sodium chloride salt particles were added, and magnetic stirring was performed again for 5 minutes to obtain a uniform PV-PDMS prepolymer solution. The PV-PDMS prepolymer solution was uniformly coated on the surface of the substrate and compacted, and cured at 80°C and normal pressure for 4 hours to obtain a porous coating containing salt particles. The porous coating containing salt particles was then placed in an 80°C water bath for 72 hours, and the water in the water bath needed to be replaced every 8 hours to completely remove the salt particles. After that, it was dried in a blast drying oven at 80°C for 4 hours to obtain a porous coating. Finally, the ionic liquid was completely immersed in the ionic liquid for 6 hours to obtain the porous organosilicon anti-icing coating impregnated with the ionic liquid.

[0067] The obtained prepolymer solution (6:4:1) is directly cured to obtain a cross-linked polydimethylsiloxane coating. At -20°C, the result of ice adhesion strength test of this example is 67.73±2.90 kPa.

[0068] Example 4

[0069] 1.2g of polydimethylsiloxane, 1.8g of monovinyl monohydrogen-terminated polydimethylsiloxane, and 0.3g of cross-linking agent were added to a beaker, and a mixed solution was prepared after magnetic stirring for 5 minutes. (If the mixed solution is directly cured at 80°C and normal pressure for 4 hours, a cross-linked polydimethylsiloxane coating obtained by direct curing of a prepolymer solution with a ratio of 4:6:1 can be obtained.) Then 13.2g of sodium chloride salt particles were added, and magnetic stirring was performed again for 5 minutes to obtain a uniform PV-PDMS prepolymer solution. The PV-PDMS prepolymer solution was uniformly coated on the surface of the substrate and compacted, and cured at 80°C and normal pressure for 4 hours to obtain a porous coating containing salt particles. The porous coating containing salt particles was then placed in an 80°C water bath for 72 hours, and the water in the water bath needed to be replaced every 8 hours to completely remove the salt particles. After that, it was dried in a blast drying oven at 80°C for 4 hours to obtain a porous coating. Finally, the ionic liquid was completely immersed in the ionic liquid for 6 hours to obtain the porous organosilicon anti-icing coating impregnated with the ionic liquid.

[0070] The obtained prepolymer solution (4:6:1) is directly cured to obtain a cross-linked polydimethylsiloxane coating. At -20°C, the result of the ice adhesion strength test of this example is 48.3±5.00 kPa.

[0071] Example 5

[0072] 0.6g of polydimethylsiloxane, 2.4g of monovinyl monohydrogen-terminated polydimethylsiloxane, and 0.3g of cross-linking agent were added to a beaker, and a mixed solution was prepared after magnetic stirring for 5 minutes. (If the mixed solution is directly cured at 80°C and normal pressure for 4 hours, a cross-linked polydimethylsiloxane coating obtained by direct curing of a prepolymer solution with a ratio of 2:8:1 can be obtained.) Then 13.2g of sodium chloride salt particles were added, and magnetic stirring was performed again for 5 minutes to obtain a uniform PV-PDMS prepolymer solution. The PV-PDMS prepolymer solution was uniformly coated on the surface of the substrate and compacted, and cured at 80°C and normal pressure for 4 hours to obtain a porous coating containing salt particles. The porous coating containing salt particles was then placed in an 80°C water bath for 72 hours, and the water in the water bath needed to be replaced every 8 hours to completely remove the salt particles. After that, it was dried in a blast drying oven at 80°C for 4 hours to obtain a porous coating. Finally, the ionic liquid was completely immersed in the ionic liquid for 6 hours to obtain the porous organosilicon anti-icing coating impregnated with the ionic liquid.

[0073] The obtained prepolymer solution (2:8:1) is directly cured to obtain a cross-linked polydimethylsiloxane coating. At -20°C, the result of the ice adhesion strength test of this example is 65.4±4.42 kPa.

[0074] The ionic liquid-impregnated porous organosilicon anti-icing coating material prepared by the present invention solves the problem of high ice adhesion strength of traditional polydimethylsiloxane polymer anti-icing coatings. In addition, the anti-icing porous coating material has multiple properties, including high compressibility, hydrophobicity, low surface energy, swelling, hydrophobicity and ice resistance, especially in anti-icing. It can extend the freezing time of water droplets by 6.4 times (compared to traditional PDMS coatings) at a low temperature of -20°C, and can achieve low ice adhesion with the help of near-ionic liquids.

[0075] In the description of this specification, the description with reference to the terms "embodiment", "example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. In addition, those skilled in the art can combine or combine different embodiments or examples described in this specification and the features therein without causing any contradiction.

[0076] Although the above content has shown and described the embodiments of the present invention, it can be understood that the above embodiments are exemplary and cannot be understood as limitations of the present invention. Ordinary technicians in the field can change, modify, replace, modify and other update operations on the above embodiments within the scope of the present invention.

Claims

1. An ionic liquid impregnated porous organosilicon anti-icing coating, characterized in that: The coating is a polymer prepared by using polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane, a crosslinking agent, salt particles and an ionic liquid; The polydimethylsiloxane undergoes a polycondensation reaction with the vinyl groups on the monovinyl monohydrogen-terminated polydimethylsiloxane and the silicon-hydrogen bonds on the crosslinking agent to form a polymer.

2. The ionic liquid impregnated porous organosilicon anti-icing coating according to claim 1, characterized in that: The salt particles are sodium chloride particles; the ionic liquid is 1-octyl-3-methylimidazolium tetrafluoroborate; and the polymer is a porous polydimethylsiloxane composite polymer with controlled crosslinking density or crosslinking modulus prepared by using polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane, a crosslinking agent, sodium chloride salt particles and ionic liquid.

3. An ionic liquid impregnated porous organosilicon anti-icing coating, characterized in that: The coating is a polymer prepared by using polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane, a crosslinking agent, salt particles and an ionic liquid; Among them, polydimethylsiloxane undergoes a condensation reaction with monovinyl monohydrogen-terminated polydimethylsiloxane and a crosslinking agent to form a polymer; the salt particles are sodium chloride salt particles; the ionic liquid is 1-octyl-3-methylimidazole tetrafluoroborate; and the polymer is a porous polydimethylsiloxane composite porous polymer with regulated crosslinking density or crosslinking modulus prepared by using polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane, a crosslinking agent and salt particles.

4. The ionic liquid impregnated porous organosilicon anti-icing coating according to any one of claims 1 to 3, characterized in that: The ratio of polydimethylsiloxane, monovinyl monohydrogen-terminated polydimethylsiloxane and crosslinking agent is (10-a):a:1, wherein a is the ratio of monovinyl monohydrogen-terminated polydimethylsiloxane added, and a=2-8.

5. A method for preparing an ionic liquid impregnated porous organosilicon anti-icing coating, the preparation method comprising the following steps: S1. The polydimethylsiloxane, the monovinyl monohydrogen-terminated polydimethylsiloxane and the crosslinking agent are completely mixed under magnetic stirring conditions to obtain a mixed solution; S2. adding sodium chloride salt particles to the mixed solution, and obtaining a uniform porous polydimethylsiloxane coating prepolymer solution after magnetic stirring; S3. The porous polydimethylsiloxane coating prepolymer solution is heated to obtain a porous polydimethylsiloxane salt-containing coating; S4. After removing salt particles from the porous polydimethylsiloxane salt-containing coating in a water bath at a predetermined temperature, the porous coating is dried in an oven to obtain an anti-icing porous coating; S5. The porous polydimethylsiloxane coating after removing the salt particles is dried in an oven; S6. Completely immerse the dried porous polydimethylsiloxane coating in the ionic liquid solution, and obtain the liquid-infiltrated porous polydimethylsiloxane coating after complete swelling.

6. The method for preparing an ionic liquid impregnated porous organosilicon anti-icing coating according to claim 5, characterized in that: In step S1, the ratio of polydimethylsiloxane, monovinyl monohydrogen terminated polydimethylsiloxane and crosslinking agent is (10-a):a:1, wherein a is the ratio of monovinyl monohydrogen terminated polydimethylsiloxane added, and a=2-8.

7. The method for preparing an ionic liquid impregnated porous organosilicon anti-icing coating according to claim 5, characterized in that: In step S2, the mass ratio of sodium chloride salt particles to the mixed solution is 4:

1.

8. The method for preparing an ionic liquid impregnated porous organosilicon anti-icing coating according to claim 5, characterized in that: In steps S1 and S2, the magnetic stirring treatment parameters are as follows: the mixed solution is treated in a magnetic stirrer at 800-1000 rpm for 5 minutes; the heating parameters in step S3 are as follows: the heating temperature of the porous polydimethylsiloxane coating prepolymer is set to 60-80°C for 4-6 hours to obtain a porous polydimethylsiloxane salt-containing coating; the predetermined temperature water bath in step S4: the porous polydimethylsiloxane salt-containing coating is treated in a water bath at 60-80°C for 3 days, wherein the water used in the water bath is replaced every 8 hours; the drying parameters in step S5 are as follows: drying is carried out in a blast drying oven at a temperature of 60-80 degrees Celsius for 4 hours; the ionic liquid infiltration conditions in step S6 are as follows: infiltration in 1-octyl-3-methylimidazole tetrafluoroborate liquid for 4-8 hours.

9. The method for preparing an ionic liquid impregnated porous organosilicon anti-icing coating according to claim 5, characterized in that: The polydimethylsiloxane is a chain polymer, namely Sylgard 184; the monovinyl monohydrogen terminated polydimethylsiloxane is a chain polymer, and its average viscosity is 40-60 cSt.

10. The use of the ionic liquid impregnated porous organosilicon anti-icing coating according to any one of claims 1 to 3, characterized in that: The coating is applied to electronic components and / or structural parts in the aviation field, marine engineering, power industry and / or aerospace field that need to work in a cold environment below 0°C.

Citation Information

Patent Citations

  • Method for constructing long-lasting hydrophobic self-cleaning surfaces on plurality of material substrates

    CN109957327A

  • Solid-liquid filled low-surface-energy smooth functional material and preparation method thereof

    CN111825984A

  • Flexible composite dielectric hydrophobic membrane capable of driving fluid at low voltage and preparation method and application of flexible composite dielectric hydrophobic membrane

    CN115521493A

  • Antistatic organic silicon release coating as well as preparation and use methods thereof

    CN117795009A

  • Rapid cure silicone lubricious coatings

    US20130122314A1